Tradução, adaptação e evidência de validade de questionário e avaliação do comportamento e atitudes dos pais sobre transtorno específico de aprendizagem - Marcela Sena Braga (2020)
Considering the importance of the family as the first social nucleus where the child begins to build his learnings, this work was divided into two studies and its two phases. The Study 1 (phase 1) aimed to translate and adapt the “Questionnaire on Specific Learning Disorder (EHTF, 2010) - for parents” to Brazilian reality, using the procedure recommended in the literature. In its phase 2, the instrument produced – “Questionnaire on Specific Learning Disorder (EHTF, 2010) – Brazilian version for parents” – was applied to a sample of 273 parents to underand behavior, such as attitudes and gaps related to the front four dimensions theory on Specific Learning Disorder (SLD): 1. Knowledge, 2. Reaction to suspicion, 3. Information search and 4. Public policies. There was a lack of knowledge and gaps in elementary concepts in the area, the presence of stigmas, great concern in the face of the suspected conditions, lack of knowledge about the quality of schools and public policies, and, finally, lack of communication between parents and teachers. In Study 2 (phase 1 and phase 2), the instrument was subjected to factor analysis of the main component and factor exploratory analysis. Good indicator were found for the total itens of the questionnaire (cronbach's alpha: 0.93) and by dimension, in wich values were satisfactory, except for “public policy”, where the internal consistency index was considerably lower (cronbach's alpha: 0.235). Finally, after the study of phase 2, the searchers identified the items of the questionnaire that correlate more strongly with each other, it was suggested to remove questions that did not show good loading, as well as to improve items that showed insufficient values. A confirmatory analysis selected from RMSEA has the value of 0,052, considered aceptable and the Tucker Lewis index of 0,847, is at the borderline.